Molecular dynamics simulations of confined liquids in nanochannels with rough walls - Papanikolaou, Michail (Cranfield University, 2017)
During the past few decades Micro-Electromechanical systems (MEMS) have been increasingly used in various engineering domains ranging from electronics to biological sciences as nowadays they can be massively produced in numerous shapes and with various compositions. Additionally, the development of the manufacturing techniques has allowed MEMS to be easily integrated into devices and expand their applications as sensors and actuators. The future of MEMS seems to be more than promising; however the small scales involved in this type of devices give rise to phenomena that cannot be treated by continuum simulations such as Computational Fluid Dynamics (CFD) or Computational Structural Dynamics (CSD). On the contrary, Molecular Dynamics (MD) Simulations are considered to be an effective approach in investigating the flow behaviour and the rheological properties of liquids in the nanoscale. The aim of this PhD project is to establish and implement Molecular Dynamics Models for the investigation of nano-scale liquid flows and the fluid properties in nanochannels with rough walls. This thesis uses MD to investigate the effect of nano-scale roughness on the slip length, the fluid viscosity and the Kapitza resistance. Rough nanochannel walls have been modelled with the help of the multivariate Weierstrass - Mandelbrot (W-M) function which has been used in the past to describe fractally rough surfaces being common in nature. A number of different approaches have been used to extract the aforementioned thermodynamic and flow properties including Equilibrium Molecular Dynamics (EMD) and Non-Equilibrium Molecular Dynamics (NEMD) Simulations. The outcomes of this research suggest that surface roughness can greatly affect the flow behaviour of highly confined liquids as well as their thermodynamic behaviour. Therefore they could potentially be used as a first step for the selection of the surface treatment and finishing techniques of MEMS devices according to the desired fluid behaviour.